All aboard the corporate socially and environmentally responsible cruise ship: A conjoint analysis of consumer choices. (13th February 2017) - Adams, Sheree-Ann; Font, Xavier; Stanford, Davina
Abstract : Purpose: The purpose of the study was to examine the relative importance of corporate social and environmental responsibility (CSER) in comparison to standard, price, duration, destination, brand and disruption using choice-based conjoint analysis (CBC). Design/methodology/approach: CBC was used as the data collection survey technique, and counts analysis for preference and hierarchical Bayes estimation (HB) for importance levels data analysis methods, from Sawtooth Software Inc. Findings: Results show that 2:1 Royal Caribbean Cruise Line cruise consumers prefer companies with CSER policies and practices. However, their actual product choice selection of cruise package attributes revealed that consumers overall placed less importance on CSER when choosing cruises. Experienced consumers were more brand image-conscious than those new to cruising, and consumers who were less price-sensitive were most willing to choose companies with CSER policies and practices. Research limitations/implications: The information provided is specifically on "what" cruise consumer preferences and importance attributes are but does not explicitly explain "why" the respondents made the choices they did. This was at the time a limitation of the software used to conduct the study. Practical implications: The Conjoint Analysis CBC Sawtooth Software pre-2014 version choice simulators do not facilitate questions that provide answers as to "why" respondents make the choices they do in the market simulations. Social implications: The knowledge contribution is of value to both academia and industry, as the quantitative statistical data on the cruise consumers' choice preferences are of value in understanding and identifying solutions/approaches towards "opening the bottleneck" that exists between private sector sustainable development practices and consumer lifestyle changes. Originality/value: This was the first time that CBC/HB was applied within academia to examine the cruise consumers' choice preferences in a UK context and also the first time that CSER was applied as a direct variable in a cruise package to determine the preference and important values of a brand in a consumer behaviour decision-making context.